COLLECTION AND DISTRIBUTION OF WHEAT, DYNAMIC OF THEPROCESS OF SHIPPING TO INTERNATIONAL MARKETS: CASE STUDY - Lagarda, Ernesto Alonso (International Journal of Supply Chain Management, 2019)
This article presents the case study developed over five months in an agrofood company from Southern Sonora. The problem detected was the lack of quantitative information for decision making in the processes of wheat collection, transport, and sales in domestic and international markets. The aim was to build a dynamic interface that would allow observing the quantitative scenarios in the distribution link. The method included the prior analysis of the processes of wheat collection and delivery at the Port of Guaymas to attend to the demands of Algeria, Nigeria, and Venezuela. This article only presents information from deliveries to Algeria as an international destination, where the demand varies from 49 thousand to 86 thousand tons of wheat annually; the organization was looking into how to concentrate all the quantitative information and make decisions based on possible modifications of their collection and delivery policies. The system dynamics methodology employing Stella Architect software generated the development of a dynamic and visual user interface that allowed them to observe each of the quantitative scenarios associated with the amount of wheat that was being moved from the wheat collection centers to the domestic and international destinations. The main conclusions are that decision making supported by a user-friendly and visual dynamic interface allows the interested parties to modify the higher priority indicators and in thus observe the scenarios according to current and future policies in wheat distribution logistics; this establishes that the system dynamics methodology is a practical and reliable development and analysis tool for solutions in the agrofood sector.